2018
DOI: 10.3390/pr6050045
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid (1-Butyl-3-Metylimidazolium Methane Sulphonate) Corrosion and Energy Analysis for High Pressure CO2 Absorption Process

Abstract: Abstract:This study explores the possible use of ionic liquids as a solvent in a commercial high-pressure CO 2 removal process, to gain environmental and energy benefits. There are two main constraints in realizing this: ionic liquids can be corrosive, specifically when mixed with a water/amine solution with dissolved O 2 & CO 2 ; and CO 2 absorption within this process is not very well understood. Therefore, scavenging CO 2 to ppm levels from process gas comes with several risks. We used 1-butyl-3-methylimida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to the Intergovernmental Panel on Climate Change (IPCC) [1], the main origin is the anthropogenic emissions of so-called greenhouse gases (GHG), due to the use of fossil fuels such as coal, oil and natural gas for the production of electricity, transportation or industrial uses, CO 2 being the most relevant among the greenhouse gases. For this reason, the use of renewables energies which reduce CO 2 emissions could be found as one of the fields most investigated in the last decade [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Intergovernmental Panel on Climate Change (IPCC) [1], the main origin is the anthropogenic emissions of so-called greenhouse gases (GHG), due to the use of fossil fuels such as coal, oil and natural gas for the production of electricity, transportation or industrial uses, CO 2 being the most relevant among the greenhouse gases. For this reason, the use of renewables energies which reduce CO 2 emissions could be found as one of the fields most investigated in the last decade [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for high-pressure applications, the usage of amine mixtures has a minimal impact on the CO 2 removal, while for low-pressure systems, it leads to a major enhancement. A similar attempt at CO 2 removal at high pressures has been reported using ionic liquids . Another study evaluated the blending of MDEA with DEA and MEA in different ratios to find out the optimum concentration of each amine blend.…”
Section: Introductionmentioning
confidence: 90%
“…A similar attempt at CO 2 removal at high pressures has been reported using ionic liquids. 16 Another study evaluated the blending of MDEA with DEA and MEA in different ratios to find out the optimum concentration of each amine blend. The study calculated the energy requirement for each blend with the lowest achievable sweet gas acid content.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages were also demonstrated by Yang et al [43]; mixing 30 wt% of MEA, 40 wt% of [bmim][BF4], and 30 wt% of H 2 O, it was possible to reduce the energy consumption by 37.2% compared to an aqueous solution of MEA. An optimal ratio between the IL and the traditional solvent exists, as found by Taimoor et al [44] when considering [bmim][MS] and MEA in their carbon dioxide capture process, developed in Aspen Hysys ® .…”
Section: Introductionmentioning
confidence: 99%